Haddam, Washington County - Hanson, Zach (Kansas State University, The Chapman Center for Rural Studies, 2012)
Haddam is a little Kansas town ten miles from the Nebraska border that has managed to survive through a slew of fires and other tragedies throughout the years. Flour factories, honey business, and a once thriving auto dealership have all stuck their stake in Haddam, Kansas and are all part of its rich history.
Zach Hanson, “Haddam, Washington County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/80.
Keywords: Burlington & Missouri Railroad; West Haddam; Washington County; Vernon Adee; Highway 36; flour mill